On the formation of hierarchical microstructure in a Mo-doped NiCoCr medium-entropy alloy with enhanced strength-ductility synergy. (15th January 2020) - He, Junyang; Makineni, Surendra Kumar; Lu, Wenjun; Shang, Yuanyuan; Lu, Zhaoping; Li, Zhiming; Gault, Baptiste
Abstract: We demonstrate the formation of a hierarchical microstructure by optimized combination of Mo-doping and thermo-mechanical processing in a NiCoCr medium-entropy-alloy (MEA) that results in a significant improvement in yield-strength (~775 MPa) and ultimate-tensile-strength (~1200 MPa) with an elongation to fracture up to 35%. Addition of Mo slows down the recrystallization kinetics of the cold-rolled alloy at 700 °C. After 4 h annealing, the microstructure comprises soft recrystallized and hard non-recrystallized zones, dispersed σ precipitates, annealing twins and retained stacking faults/nanotwins that are shown to contribute to the overall mechanical behavior. Graphical abstract: Unlabelled Image